PENGUATAN PENDIDIKAN ABAD 21 DALAM PEMBELAJARAN MUSIK ANSAMBEL - Rehuela, Abigail; Tarwiyah Adi Sam, Tuti (Jurnal Penelitian Musik, 2024)
The purpose of this research is to know, and describe the strengthening of 21st Century Education through ensemble music learning through ensemble music learning. The research method used in this research is literature study, with literature, with data collection techniques in the form of; literature study, interviews. The results of the research obtained that 21st century education and music ensemble learning have many elements in common, so that both have the same elements, so both are suitable and build each other. Education of the 21st century is not education that is made suddenly, the education has been designed at the time of the 2013 curriculum. Education was already designed when the 2013 curriculum was running. 21st century education is made with learning that depends on students (student centred), besides that, the role of the teacher remains important, to facilitate students. Skills applied in 21st century education, namely; critical thinking, creativity, collaboration, communication. With the competencies that competencies that have been designed and applied from the beginning, it can be ascertained that by mastering these things, learners can be more mastering these things, students can be more responsive to changes and developments in the changes and developments of the times, not only at school, but also in their environment, and even until the learners grow up.